Application of extreme learning machine with 3D image description for medical objects segmentation - Yang, Jing (2012)
Medical image segmentation has many applications in health care industry. This project aims at applying the newly developed learning algorithm - Extreme Learning Machine (ELM) to 3D-medical images to segment liver image based on texture features. Further to liver segmentation, a comparison is made between direct ELM segmentation and ELM segmentation with adaboosting on liver tumor segmentation. A study of Active Shape Model (ASM) is carried out to regulate the shape obtained in liver segmentation.